Penerapan Service Quality pada Kajian Aspek Pasar: Studi Kelayakan Usaha Cafe Bukit Soka - Wibowo, Dianta Ricky; Setyanti, Dina Budi; Putri, Evellyn Diva; Atahau, Apriani Dorkas Rambu (Universitas Methodist Indonesia, 2024)
After the Covid-19 pandemic, Wisma Baptis Bukit Soka Salatiga, which is supported by the Indonesian Baptist Foundation, has plans to establish a new business, Cafe Bukit Soka. This community service activity was carried out to assist the Indonesian Baptist Foundation in observing the establishment of a new business, Cafe Bukit Soka. Observations were carried out by reviewing market aspects using the service quality method while also conducting direct observations in the field. In the survey that has been carried out, service quality indicators are used which consist of physical evidence, reliability, responsiveness, guarantee and attention. The results of observations through a market survey obtained 50 respondents who had the perception that Cafe Bukit Soka would provide adequate facilities, be responsive to consumer complaints and desires, reliable in serving consumers, guarantee safety and comfort, and pay attention to every consumer's needs. This analysis was prepared in the form of a report which was then submitted to Wisma Bukit Soka Salatiga to be used as a reference in establishing a new business, Cafe Bukit Soka.